The exposure level of environmental harmful substances related to the secondhand smoke in Korean non-smoker adults: data from the second Korean National Environmental Health Survey (KoNEHS 2012–2014): a cross-sectional study - Kim, Sang Woo (Ann Occup Environ Med, 2019)
BACKGROUND: We aimed to find the exposure level of environmental harmful substances related to the secondhand smoke (SHS) using a nationally representative data of the general population in Korea. METHODS: Total 3,533 people were included in this study. We compared the proportion exceeding 95 percentile of the concentrations of harmful substances by sex according to SHS exposure. 16 kinds of substances related to tobacco smoke were analyzed including heavy metals, polycyclic aromatic hydrocarbons, volatile organic compounds, and environmental phenol. For 16 kinds of substances, the odds ratios (ORs) for exceeding 95 percentile of each harmful substance were calculated by multiple logistic regression according to SHS exposure. Age, education level, marital status, body mass index, drinking, and exercise were adjusted as covariates. Cotinine level was additionally adjusted to increase reliability of our results. RESULTS: SHS was associated with high exposure of mercury, methylhippuric acid, fluorene, and cotinine. In women, SHS was associated with mercury, methylhippuric acid, fluorene, and cotinine, while in men, it was associated with cotinine. After adjusting covariates, ORs of blood mercury, methylhippuric acid and hydroxyfluorene in the exposed gruop were greater than that in the non-exposed group. Especially in female, methylhippuric acid and hydroxyfluorene showed consistent result. CONCLUSIONS: Our finding demonstrates that SHS is related to several harmful substances. Therefore, to reduce the health effects of SHS, it is necessary to educate and publicize the risk of SHS. Future studies are necessary to more accurately analyze factors such as exposure frequency, time, and pathway of SHS.